Super Structural Teaching Kits as Teaching Aid Materials for Construction Technology Students - YEE, MEI HEONG; Ismail, Asyraf; Mohd Shah, Syazwani Zafirah (Research and Innovation in Technical and Vocational Education and Training, 2021)
Teaching Aids Materials (TAM) is an important thing in a teaching and learning session as it can stimulate student’s interest in learning because TAM is either in electronic or non-electronic form is an important support tool to increase the understanding of students and their interest in learning. This study discusses the use of teaching kits as TAM to assist teachers in implementing better and more effective teaching and learning sessions in the superstructure topic. The use of TAM is very necessary nowadays because it is a one-century learning method that can attract students during teaching and learning sessions. This study aims to know the suitability of teaching kit design, suitability of using the kit material, and functional applicability of teaching kits as TAM. The research design used in this study is in the form of product development and quantitative approach which uses the questionnaire form as a research instrument for data collection. The sample for the study was 20 lecturers from the Tanah Merah Vocational College and Kuala Krai Vocational College. The findings of the study showed that the use of the superstructural teaching kits could improve the quality and be suitable to be used in the teaching and learning session of the superstructure topic in a vocational college.Keywords: teaching kits, teaching aid material, suitability of kit design, 21st-century learning, super structure, vocational college